2018
DOI: 10.1002/adma.201804556
|View full text |Cite
|
Sign up to set email alerts
|

A Tunable Optofluidic Microlaser in a Photostable Conjugated Polymer

Abstract: The optofluidic laser has become an important platform for biological sensing and medical diagnosis. To date, fluorescent dyes and proteins have been widely utilized as gain materials for biological analysis due to their good biocompatibility, but the limited photostability restricts their reliability and sensitivity. Here, an optofluidic microlaser with an ultralow threshold down to 7.8 µJ cm−2 in the ultrahigh‐Q whispering‐gallery microcavity, which is filled with a biocompatible conjugated polymer, is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…There exist some ways to improve the stability of conjugated polymer laser materials, for example, Tang et al investigated the photostability of conjugated polymer microlasers. Compared with traditional dye laser materials, the conjugated polymer substituted with electrophilic cyano is much more photostable [24].…”
Section: Laser Process Of Conjugated Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…There exist some ways to improve the stability of conjugated polymer laser materials, for example, Tang et al investigated the photostability of conjugated polymer microlasers. Compared with traditional dye laser materials, the conjugated polymer substituted with electrophilic cyano is much more photostable [24].…”
Section: Laser Process Of Conjugated Polymersmentioning
confidence: 99%
“…The latest works on conjugated polymer lasers come from 2018. In 2018, Xiao et al demonstrated an optofluidic microlaser using a biocompatible conjugated polymer (poly[2-methoxy-5-(2- ethylhexyloxy)-1,4-(1-cyanovi-nylene-1,4-phenylene)]) (CN-PPV) as gain materials, due to the electrophilic CN-group substituent, the photostability and lasing stability of the whole conjugated polymer were improved greatly compared with a typical dye laser [24].…”
Section: Introductionmentioning
confidence: 99%
“…There is still significant progress to be made in the development of WGM microresonator structures, such as deformed microresonators, 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 endoscopic sensing probes, 145 , 146 and WGM sensors in chip-based microfluidics channels. 147 Not only will these lead to further improvement in device sensitivity but they will also allow for the detection of analytes that are beyond the reach of current techniques.…”
Section: Discussionmentioning
confidence: 99%
“…One of the possible ways to address this problem is the replacement of dyes with polymers 84 . For example, an optofluidic microlaser with an ultralow threshold down to 7.8 µJ cm −2 in an ultrahigh‐Q WGM microcavity filled with a biocompatible conjugated polymer has been demonstrated 85 . This conjugated polymer exhibits a significant enhancement in lasing stability compared with Nile red.…”
Section: Review Of Gain Media In Wgm Microlasers For Sensingmentioning
confidence: 99%